Guidelines for the integrity management of valves for the upstream and downstream industries. (Energy Institute, 2019)
This guidance has been written to support valve integrity management for the top-side activities of both the upstream and downstream petroleum industries. This includes hydrocarbon and hazardous systems, critical utilities, fire systems, and steam. This guidance covers the following valve types: gate valves; globe (on/off) valves; diaphragm and pinch valves; plug valves; ball valves; butterfly valves; globe and angle control valves; choke valves, and self-acting regulating valves.This document includes guidance on specification and selection, installation and commissioning, operation, maintenance, inspection condition monitoring, proof testing, and remedial actions. It also aims to provide guidance on issues such as knowledge, training and understanding, management of change (MoC), Safe Systems of Work (SSOW), and lessons learned and agreed good practices. The target audience for this guidance document are personnel working within top-side activities of both the upstream and downstream petroleum industries, including: site managers; supervisors; technicians; operators; process system designers, and valve manufacturers and suppliers.